Current State and Development Forecast of Dairy Market - AIMURZINA, Baglan; KAMENOVA, Mazken; KAIDAROVA, Lyazzat; TOLUSBAYEVA, Marzhan; NURGABYLOV, Murat; DOSHAN, Almagul (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
The article discusses the place of the dairy market in the structure of the food market of Kazakhstan, considered the state and problems of sustainable development of its production. Various approaches to forecasting its development had analyzed. Extrapolation and exponential smoothing methods are used as the most appropriate, allowing, according to the authors, to take into account various trends in the sphere of production, distribution and consumption of food products.